Fabrication of visible-light responsive CQDs/Cu2O nanocomposite for CO2 photoreduction - Kulandaivalu, Tharani; Abdul Rashid, Suraya; Sabli, Nordin; Tan, Tong Ling (2018)
Semiconductor-carbonaceous integrated materials are gaining a vast demand in photocatalytic reactions for their facscinatng combined features to attain promising photocatalytic results. In this work, bluefluorescent carbon quantum dots (CQDs) were synthesized via a facile top-down hydrothermal method using EFB biochar of oil palms as the carbon source. The CQDs were incorporated together with copper (I) oxide (Cu2O) via a simple wet impregnation method to form CQDs/Cu2O nanocomposite. High resolution transmission electron microscopy (HRTEM) confirmed the successful deposition of CQDs onto the surface of Cu2O nanoparticles. The CQDs/Cu2O nanocomposite showed a considerable improvement in the CO2 photoreduction with an enhancement of 54% compared to the pure Cu2O, due to the retardation of the recombination of charge carriers.